Trade costs, trade balances and current accounts an application of gravity to multilateral trade ; presented at CESifo area conference on macro, money & International finance, February 2005 - Fazio, Giorgio; MacDonald, Ronald 1955-; Mélitz, Jacques (CES, 2005)
In this paper we test the well-known hypothesis of Obstfeld and Rogoff (2000) that trade costs are the key to explaining the so-called Feldstein-Horioka puzzle. Using a gravity framework in an intertemporal context, we provide strong support for the hypothesis and we reconcile our results with the so-called home bias puzzle. Interestingly, this requires a fundamental revision of Obstfeld and Rogoff’s argument. A further novelty of our work is in tying bilateral trade behavior to desired aggregate trade balances and desired intertemporal trade.
Literaturverz. S. 25 - 27. - Auch im Internet unter den Adressen www.SSRN.com und www.CESifo-group.de verfügbar
Keywords: Konferenzschrift